Positive electrode active material precursor and preparation method and application thereof
By preparing the positive electrode active material precursor of secondary large particles assembled from small secondary particles, the problems of wide particle size distribution and small specific surface area of the positive electrode material precursor of sodium ion battery are solved, and high specific capacity and magnification performance are achieved The electrochemical performance of the battery is significantly improved.
Patent Information
- Application Number
- CN202411361208.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-26
- Publication Date
- 2024-12-17
AI Technical Summary
The precursors of the existing sodium ion battery positive electrode material have problems with wide particle size distribution and small specific surface area during the sintering process, which leads to changes in structure and performance, making it difficult to take into account both specific capacity and rate performance.
By preparing the positive electrode active material precursor of secondary large particles assembled from secondary small particles, the morphological structure and particle size parameters are defined, ensuring a narrow particle size distribution width and a large specific surface area, avoiding overburning and improving reaction activity , realize single crystallization.
The excellent energy density and lithium ion transmission efficiency of the positive electrode material are achieved, and the specific capacity and rate performance are improved.
Smart Images

Figure CN119143197A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of secondary batteries, and in particular to a positive electrode active material precursor and a preparation method and application thereof. Background Art
[0002] Sodium-ion batteries have gradually become a hotspot in the research and development of battery technology in recent years due to their advantages such as high safety, abundant raw materials and low cost. They are widely used in low-speed electric vehicles and energy storage devices. The positive electrode material is one of the important components of the battery and an important factor in determining the electrochemical performance of the battery. The performance of the positive electrode material of sodium-ion batteries mainly depends on the precursor.
[0003] At present, the precursors of positive electrode materials for sodium ion batteries are mainly prepared by intermittent and continuous methods. The positive electrode material precursors prepared by these methods have the problems of wide particle size distribution and small specific surface area. Among them, the precursor particle size distribution is wide, and there are some particles with too small particle size. During the sintering process, they are overheated and over-burned, resulting in changes in their structure and performance, affecting the specific capacity of the positive electrode material; the precursor has a small specific surface area, and the reaction activity is not high during the sintering process, making it difficult to achieve single crystallization, which is not conducive to improving the rate performance of the positive electrode material.
[0004] Therefore, how to provide a positive electrode active material precursor that can improve both specific capacity and rate performance is a technical problem that needs to be solved urgently in this field. Summary of the invention
[0005] The main purpose of the present invention is to provide a positive electrode active material precursor and a preparation method and application thereof, so as to solve the problem that the existing precursors are difficult to balance specific capacity and rate performance.
[0006] In order to achieve the above-mentioned purpose, the first aspect of the present invention provides a positive electrode active material precursor, which includes secondary large particles assembled from secondary small particles, and the secondary small particles are assembled from primary particles; wherein the ratio of the diameter of the secondary small particles to the diameter of the secondary large particles is (0.09~0.2):1.
[0007] By limiting the morphology structure and particle size parameters of the positive electrode active material precursor, the particle size distribution width and specific surface area of the positive electrode active material precursor can be improved. While ensuring that it has a narrow particle size distribution width, the specific surface area can also be increased. In the subsequent sintering to prepare the positive electrode active material, overburning can be avoided. At the same time, the high reaction activity is conducive to achieving single crystallization, thereby improving both specific capacity and rate performance.
[0008] Further, the primary particles are flaky whiskers with a length of 300 to 400 nm, a width of 200 to 350 nm, and a thickness of 50 to 70 nm; and / or the specific surface area of the positive electrode active material precursor is 20 to 40 m 2 / g; and / or, the particle size distribution width SPAN value of the positive electrode active material precursor is 0.8 to 1.35.
[0009] By limiting the specific surface area of the positive electrode active material precursor within the above range, it is possible to ensure that there are enough active sites that can participate in the reaction, control the reaction activity within an appropriate range, and help achieve single crystallization.
[0010] By limiting the particle size distribution width SPAN value of the positive electrode active material precursor within an appropriate range, the particle size distribution width is narrower and more concentrated, which is beneficial to improving the tap density of the positive electrode active material precursor and can provide a certain mechanical strength and higher energy density for the subsequently prepared positive electrode active material.
[0011] Furthermore, the diameter of the secondary small particles is 0.3-1 μm; and / or the diameter of the secondary large particles is 3-7 μm.
[0012] Furthermore, the tap density of the positive electrode active material precursor is 1.1 to 1.8 g / cm 3 .
[0013] By limiting the tap density of the positive electrode active material precursor to be within the above range, a certain mechanical strength and a higher energy density can be provided for the subsequently prepared positive electrode active material.
[0014] Furthermore, the chemical formula of the positive electrode active material precursor is Ni x Fe y Mn 1-x-y (OH) 2 , among which, 0.01≤x≤0.8, 0.01≤y≤0.8, 0.01≤1-xy≤0.8.
[0015] The second aspect of the present invention provides a method for preparing a cathode active material precursor provided in the first aspect, comprising the following steps: mixing a metal salt solution, a precipitant and a complexing agent to form a reaction slurry, and subjecting the reaction slurry to a coprecipitation reaction to obtain a cathode active material precursor; wherein, in the coprecipitation reaction, the rotation speed of the reaction slurry is controlled to be 50 to 500 rpm, the pH value is 7 to 12, and the reaction temperature is 30 to 80°C.
[0016] Furthermore, the concentration of metal ions in the metal salt solution is 0.5 to 4 mol / L; and / or the complexing agent includes at least one of ammonia water, EDTA, triethanolamine, ammonium citrate, glycine, sodium citrate, tartaric acid, citric acid, ethylenediamine, ethanolamine, and acetic acid; and / or the precipitating agent includes at least one of sodium carbonate, sodium bicarbonate, ammonium bicarbonate, sodium oxalate, sodium hydroxide, and potassium hydroxide.
[0017] Furthermore, the molar ratio of the precipitant to the metal ions in the metal salt solution is (1-2.2):1.
[0018] Furthermore, after the coprecipitation reaction, the method further includes the following steps: centrifugally washing the material after the coprecipitation reaction in an alkali solution of 0.8 to 8 mol / L at a speed of 5 to 20 rpm, then washing with distilled water at the same speed, and finally drying the washed material at 60 to 150° C. for 10 to 40 hours.
[0019] The third aspect of the present invention provides a sodium battery positive electrode material, which is prepared by sintering raw materials including a positive electrode active material precursor, wherein the positive electrode active material precursor includes the positive electrode active material precursor of the first aspect or the positive electrode active material precursor prepared by the preparation method provided by the second aspect.
[0020] By sintering the positive electrode active material precursor with specific morphology and structure, a single crystal positive electrode active material with excellent energy density and lithium ion transmission efficiency can be obtained, so that the battery assembled from the single crystal positive electrode active material has excellent specific capacity and rate performance.
[0021] The implementation of the present invention has at least the following beneficial effects:
[0022] The positive electrode active material precursor provided by the present invention improves the particle size distribution width and specific surface area of the positive electrode active material precursor by limiting the morphological structure and particle size parameters of the positive electrode active material precursor. While ensuring that it has a narrow particle size distribution width, it can also increase the specific surface area. During the subsequent sintering to prepare the positive electrode active material, overburning can be avoided. At the same time, the reaction activity is high, which helps to achieve single crystallization, thereby improving both specific capacity and rate performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] The drawings constituting a part of the present application are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute an improper limitation of the present invention. In the drawings:
[0024] Figure 1 This is a scanning electron microscope image of the precursor in Example 1 of the present invention;
[0025] Figure 2 This is a scanning electron microscope image of the precursor in Example 2 of the present invention;
[0026] Figure 3 This is a scanning electron microscope image of the precursor in Comparative Example 1 of the present invention;
[0027] Figure 4 This is a scanning electron microscope image of the precursor in Comparative Example 2 of the present invention. DETAILED DESCRIPTION
[0028] It should be noted that, in the absence of conflict, the embodiments and features in the embodiments of the present application can be combined with each other. The present invention will be described in detail below in conjunction with the embodiments.
[0029] As described in the background technology, the existing precursor has the problem of wide particle size distribution and small specific surface area. In order to solve the above technical problems, the present application provides a positive electrode active material precursor, which includes secondary large particles assembled from secondary small particles, and the secondary small particles are assembled from primary particles; wherein the ratio of the diameter of the secondary small particles to the diameter of the secondary large particles is (0.09-0.2):1.
[0030] The positive electrode active material precursor includes a plurality of secondary large particles, wherein the secondary large particles are aggregates assembled from secondary small particles, and the secondary small particles are aggregates assembled from a number of primary particles. The secondary small particles can be aggregated into secondary large particles by agglomeration, adsorption, nucleation, etc., so as to ensure that the particle size of the positive electrode active material precursor is uniform and avoid the occurrence of particles with too small a particle size.
[0031] The ratio of the diameter of the secondary small particles to the diameter of the secondary large particles is (0.09-0.2):1, for example, 0.09:1, 0.1:1, 0.15:1, 0.16:1, 0.18:1, 0.2:1 or a range consisting of any two of them. The secondary small particles can be obtained through a scanning electron microscope (SEM) image, and the diameter of the secondary large particles can be obtained by using a particle size analyzer to obtain an average diameter, i.e., D50 particle size. Specifically, at least 50 secondary small particles are selected from the SEM image, and the sizes of the secondary small particles are measured respectively and the average value is calculated to obtain the diameter of the secondary small particles.
[0032] According to the research of the present invention, the positive active material precursor provided by the present invention has the advantages of narrow particle size distribution width and large specific surface area. This is because, by limiting the morphological structure and particle size parameters of the positive active material precursor, ensuring the size uniformity of the primary particles, and making them closely packed, the space utilization rate can be maximized, the specific surface area of the positive active material precursor can be increased, the uniformity of the size of the secondary large particles can be ensured, and the particle size distribution width is narrow. When the positive active material precursor is used for sintering to prepare the positive active material, overburning can be avoided, and the reaction activity is high, which helps to achieve single crystallization, thereby taking into account the improvement of specific capacity and rate performance.
[0033] In some embodiments, the primary particles are flaky whiskers with a length of 300-400 nm, a width of 200-350 nm, and a thickness of 50-70 nm. The size of the primary particles can be obtained from a scanning electron microscope (SEM) image. Specifically, at least 200 primary particles are selected from the SEM image, and the length, width, and thickness of each are measured and the average value is calculated to obtain the length, width, and thickness of the primary particles.
[0034] The positive electrode active material precursor of the present invention can be mixed with a lithium source or a sodium source and sintered to obtain a positive electrode active material. The specific surface area and morphology of the positive electrode active material directly determine the specific surface area and morphology of the positive electrode active material. In some embodiments, the specific surface area of the positive electrode active material precursor is 20 to 40 m 2 / g, for example 20m 2 / g, 25m 2 / g, 30m 2 / g, 35m 2 / g, 40m 2 By limiting the specific surface area of the positive electrode active material precursor within the above range, it is possible to ensure that there are enough active sites that can participate in the reaction, control the reaction activity within an appropriate range, and help achieve single crystallization.
[0035] Among them, the specific surface area can be determined by nitrogen adsorption dynamic chromatography. Under certain temperature and pressure conditions, gas molecules are adsorbed on the sample surface, and the amount of adsorbed gas is measured to obtain the adsorption isotherm. According to the adsorption isotherm, the BET model is used for calculation to obtain the value of the specific surface area.
[0036] In some embodiments, the particle size distribution width SPAN value of the positive electrode active material precursor is 0.8 to 1.35. By limiting the particle size distribution width SPAN value of the positive electrode active material precursor to a suitable range, the particle size distribution width is narrower and more concentrated, which is beneficial to improving the tap density of the positive electrode active material precursor, and can provide a certain mechanical strength and a higher energy density for the subsequently prepared positive electrode active material.
[0037] Specifically, the particle size distribution width of the positive electrode active material precursor substantially refers to the particle size distribution width of all secondary large particles in the positive electrode active material precursor. The positive electrode active material precursor is calculated according to the formula (D90-D10) / D50, where D10 is the particle size corresponding to 10% of the volume cumulative distribution percentage of the sample, D50 is the particle size corresponding to 50% of the volume cumulative distribution percentage of the sample, and D90 is the particle size corresponding to 90% of the volume cumulative distribution percentage of the sample.
[0038] The present invention does not limit the test method of D10, D50, and D90 of the positive electrode active material precursor, and for example, a laser particle size analyzer may be used for measurement.
[0039] The present invention does not limit the specific size of the above particles, as long as the above relationship is satisfied. For example, in some embodiments, the diameter of the secondary small particles is 0.3-1 μm, such as 0.3 μm, 0.4 μm, 0.5 μm, 0.6 μm, 0.7 μm, 0.8 μm, 0.9 μm, 1 μm or any two thereof.
[0040] In some embodiments, the diameter of the secondary large particles is 3-7 μm, for example, 3 μm, 4 μm, 5 μm, 6 μm, 7 μm or a range consisting of any two thereof.
[0041] In some embodiments, the tap density of the positive electrode active material precursor is 1.1 to 1.8 g / cm 3 , for example 1.1 g / cm 3 , 1.2g / cm 3 , 1.3g / cm 3 , 1.4g / cm 3 , 1.5g / cm 3 , 1.6g / cm 3 , 1.8g / cm 3 Or a range consisting of any two of them. The tap density refers to the compactness of the packing of crystal particles. By limiting the tap density of the positive electrode active material precursor to the above range, a certain mechanical strength and a higher energy density can be provided for the subsequently prepared positive electrode active material.
[0042] In some embodiments, the chemical formula of the positive electrode active material precursor is Ni x Fe y Mn 1-x-y (OH) 2 , among which, 0.01≤x≤0.8, 0.01≤y≤0.8, 0.01≤1-xy≤0.8.
[0043] Among them, the positive electrode active material precursor is nickel-iron-manganese-based hydroxide.
[0044] The second aspect of the present invention provides a method for preparing a positive electrode active material precursor, comprising the following steps: mixing a metal salt solution, a precipitant and a complexing agent to form a reaction slurry, and subjecting the reaction slurry to a coprecipitation reaction to obtain a positive electrode active material precursor; wherein, in the coprecipitation reaction, the rotation speed of the reaction slurry is controlled to be 50 to 500 rpm, the pH value is 7 to 12, and the reaction temperature is 30 to 80°C.
[0045] The crystallization process of crystalline materials is divided into two stages: nucleation and nuclear growth. Specifically, a crystal nucleus is first formed in the reaction solution, and then a positive electrode active material precursor with a specific size grows on the basis of the crystal nucleus. The process of forming the crystal nucleus is the nucleation stage, and the process of forming the positive electrode active material precursor with a specific size is the nuclear growth stage.
[0046] The positive electrode active material precursor of the present invention can be prepared in a reaction kettle. Specifically, a metal salt solution, a precipitant and a complexing agent undergo a coprecipitation reaction in the reaction kettle.
[0047] In the specific implementation process of the present invention, the pH of the reaction slurry can be regulated by controlling the feed flow rate of the precipitant.
[0048] Due to the coordination effect and steric hindrance effect of the complexing agent, the temperature affects the size of the complexing constant of different ions, thereby affecting the coprecipitation effect. By controlling the reaction temperature to 30-80°C, it is beneficial to obtain a precursor with the above morphology.
[0049] In some embodiments, before the metal salt solution, the precipitant and the complexing agent are pumped into the reactor, the following steps are also included: adding water as the base liquid into the reactor, blowing nitrogen, controlling the stirring speed in the reactor to 50-500 rpm, the temperature to 30-80°C, and then adding the metal salt solution, the precipitant and the complexing agent, controlling the pH value to 7-12, and continuously feeding. When the product particle size D50 in the reactor grows to the target particle size, stop feeding and the synthesis is completed.
[0050] The present invention does not limit the specific types and physical parameters of the metal salt solution, the precipitant and the complexing agent, and can be adjusted according to actual production needs. For example, the concentration of the metal ions in the metal salt solution is 0.5-4 mol / L; and / or, the complexing agent includes at least one of ammonia water, EDTA, triethanolamine, ammonium citrate, glycine, sodium citrate, tartaric acid, citric acid, ethylenediamine, ethanolamine, and acetic acid; and / or, the precipitant includes at least one of sodium carbonate, sodium bicarbonate, ammonium bicarbonate, sodium oxalate, sodium hydroxide, and potassium hydroxide.
[0051] The metal salt solution can be prepared by mixing a metal salt with water, wherein the metal salt includes but is not limited to at least one of a metal nitrate salt, a metal hydrochloride salt, and a metal sulfate salt. The metal salt includes a nickel salt, a divalent iron salt, and a manganese salt.
[0052] In the specific implementation process of the present invention, the precipitant and the complexing agent can be mixed with water to form a precipitant solution and a complexing agent solution respectively, and then the metal salt solution, the precipitant solution and the complexing agent solution are mixed to form a reaction slurry. The concentration of the precipitant in the precipitant solution is 80-120 g / L, and the concentration of the complexing agent in the complexing agent solution is 180-220 g / L.
[0053] In the above preparation process, the molar ratio of the precipitant to the metal ions in the metal salt solution is (1-2.2):1, for example, 1:1, 1.5:1, 2:1, 2.2:1 or a range consisting of any two of them.
[0054] In order to obtain the positive electrode active material precursor, a post-processing step is also included after the coprecipitation reaction, and the post-processing includes washing and drying. For example, when the material particle size D50 of the reaction slurry in the reactor reaches the target particle size, the feeding is stopped and the synthesis is completed; the reaction slurry in the reactor is collected and subjected to post-processing steps such as washing and drying to obtain the positive electrode active material precursor.
[0055] Among them, the washing treatment includes alkali washing treatment and water washing treatment. Specifically, the reaction slurry in the reactor is collected, and centrifuged, alkali washed and water washed in sequence. In some embodiments, after the coprecipitation reaction, the following steps are also included: the material after the coprecipitation reaction is centrifuged and washed in 0.8-8 mol / L alkali solution at a speed of 5-20 rpm, and then washed with distilled water at the same speed, and finally the washed material is dried at 60-150°C for 10-40 hours.
[0056] In addition, the post-processing also includes screening and demagnetization, that is, after the drying, the dried material is sequentially screened and demagnetized to finally obtain a positive electrode active material precursor.
[0057] The third aspect of the present invention provides a sodium battery positive electrode material, which is prepared by sintering raw materials including a positive electrode active material precursor, wherein the positive electrode active material precursor includes the positive electrode active material precursor provided by the first aspect or the positive electrode active material precursor prepared by the preparation method provided by the second aspect.
[0058] Specifically, the above-mentioned positive electrode active material precursor can be directly sintered with a sodium source to obtain a sodium battery positive electrode material, or the positive electrode active material precursor, a sodium source and other doping elements and / or coating elements can be mixed and then sintered to obtain a sodium battery positive electrode material.
[0059] By sintering the positive electrode active material precursor with specific morphology and structure, a single crystal positive electrode active material with excellent energy density and lithium ion transmission efficiency can be obtained, so that the battery assembled from the single crystal positive electrode active material has excellent specific capacity and rate performance.
[0060] The present application is further described in detail below in conjunction with specific embodiments. These embodiments should not be construed as limiting the scope of protection claimed in the present application.
[0061] Example 1
[0062] The method for preparing the positive electrode active material precursor of this embodiment includes the following steps:
[0063] (1) Preparation of reaction raw materials
[0064] Weigh ferrous sulfate, nickel sulfate and manganese sulfate in a molar ratio of 1:1:1, add pure water to prepare a 2 mol / L metal salt solution; prepare 100 g / L ammonia solution (complexing agent solution); prepare 200 g / L sodium hydroxide solution (precipitant solution);
[0065] (2) Preparation stage
[0066] Add pure water to the reactor, blow nitrogen into it, turn on the reactor stirrer, set the speed to 360rpm, control the temperature at 60℃, add metal salt solution, sodium hydroxide solution and ammonia solution, adjust the pH value to 11.5, and stop feeding to produce qualified materials when the particle size of the material in the reactor reaches 3.5μm; centrifuge and wash the output material, wash it with 1.25moL / L sodium hydroxide solution, and then wash it with 70-80℃ pure water; put it into a blast drying oven after unloading, dry it at 120℃ for 12h, and store it in bags after cooling; after screening, mixing and other treatments, Ni 0.334 Fe 0.333 Mn 0.333 (OH) 2 Precursor.
[0067] Example 2
[0068] The difference from Example 1 is that during the preparation stage, the rotation speed is 500 rpm and the pH value is adjusted to 11.2.
[0069] Comparative Example 1
[0070] The difference from Example 1 is that the rotation speed is 550 rpm during the preparation stage.
[0071] Comparative Example 2
[0072] The difference from Example 1 is that the pH is adjusted to 12.5 during the preparation stage.
[0073] Test example
[0074] 1. Performance of positive electrode active material precursor
[0075] (1) Primary particle and secondary small particle size test: Nano Measurer1.2 was used to test the size of primary particles and secondary small particles; 200 primary particles were selected from the SEM image, and the length, width and thickness of each particle were measured and their average values were calculated to obtain the length, width and thickness of the primary particles; 50 secondary small particles were selected from the SEM image, and their sizes were measured and their average values were calculated to obtain the diameter of the secondary small particles.
[0076] (2) Diameter test of secondary large particles: D50 particle size was tested using Malvern laser particle size analyzer;
[0077] (3) Specific surface area test: The specific surface area was determined by nitrogen adsorption dynamic chromatography;
[0078] (4) Particle size distribution width SPAN test: tested using Malvern laser particle size analyzer;
[0079] (5) Tap density test: The tap density was tested using a BT-313 tap density tester.
[0080] 2. Performance of single crystal positive electrode active materials
[0081] (1) Preparation of single crystal positive electrode active materials
[0082] The precursors of the embodiment and the comparative example are mixed according to the element molar ratio (Ni+Fe+Mn): Na=1:1.05, and the temperature is raised to 850°C in a muffle furnace at a heating rate of 5°C / min for calcination for 14 hours, and the positive electrode material of the sodium ion battery is obtained after cooling. The positive electrode material of the present invention, the binder polyvinylidene fluoride (PVDF) and the conductive carbon black (SP) are fully mixed in a weight ratio of 8:1:1, stirred to form a uniform slurry, coated on an aluminum foil current collector, dried and pressed into a pole piece. The pressed positive electrode sheet is punched, weighed, baked, and then assembled into a button battery in a vacuum glove box with a metal sodium negative electrode, a diaphragm, and an electrolyte.
[0083] (2) Cyclic performance test
[0084] At 25°C, charge at a constant current of 1C to 4.2V, then switch to a constant voltage of 4.2V and charge until the current decreases to 0.02C. After standing for 5 minutes, discharge at a discharge rate of 1C to 4.2V. Repeat this charge and discharge cycle 50 times. Measure the discharge capacity Q1 at the first cycle and the discharge capacity Q50 at the 50th cycle. Calculate the capacity retention rate Q after 50 cycles according to the following formula: Q=Q50 / Q1*100%.
[0085] (3) Rate performance test
[0086] The battery was charged and discharged at 25°C using a battery charge and discharge tester. The charge and discharge steps were as follows: 0.1C constant current charging to 4.2V, then switching to 4.2V constant voltage charging until the current decreased to 0.02C, standing for 5 minutes, and then 0.1C constant current discharging to 2.0V, recording the discharge capacity Q. 0.1C After standing for 5 minutes, charge at 0.2C constant current to 4.2V, switch to 4.2V constant voltage charging until the current decreases to 0.02C, stand for 5 minutes, discharge at 0.2C constant current to 2.0V, record the discharge capacity Q 0.2C After standing for 5 minutes, charge at 0.5C constant current to 4.2V, switch to 4.2V constant voltage charging until the current decreases to 0.02C, stand for 5 minutes, discharge at 0.5C constant current to 2.0V, record the discharge capacity Q 0.5C After standing for 5 minutes, charge at 1C constant current to 4.2V, switch to 4.2V constant voltage charging until the current decreases to 0.02C, stand for 5 minutes, discharge at 1C constant current to 2.0V, record the discharge capacity Q 1C After standing for 5 minutes, charge at 2C constant current to 4.2V, switch to 4.2V constant voltage charging until the current decreases to 0.02C, and after standing for 5 minutes, discharge at 2C constant current to 2.0V, and record the discharge capacity Q 2C .
[0087] The test results are shown in Table 1 and Table 2.
[0088] Table 1
[0089]
[0090]
[0091] Table 2
[0092]
[0093] according to Figure 1 and Figure 2It can be seen that the precursors in Example 1 and Example 2 are composed of multiple large secondary particles, the large secondary particles are composed of multiple small secondary particles, the small secondary particles are composed of multiple primary particles, the primary particle whiskers are fine, the secondary particles are relatively loosely stacked, and the gaps are large. The thickness of the primary particles is 50-70nm, the length of the primary particles is 300-400nm, the whisker size does not differ much, the uniformity is good, and the tap density and specific surface area are within an appropriate range, which makes it easier to sinter to form a single crystal positive electrode active material and improve the electrochemical properties of the positive electrode active material.
[0094] according to Figure 3 It can be seen that the thickness distribution of the primary particles of the precursor in Comparative Example 1 is uneven, with a large difference in thickness. The thickness of the primary particles is 70-300nm, and the length is 600-1000nm. The particle layers are densely stacked, which is not conducive to the sintering of the positive terminal. In addition, the specific surface area is small and cannot meet the requirements of a large specific surface area, which is not conducive to improving the electrochemical properties of the positive electrode active material.
[0095] according to Figure 4 It can be seen that the whiskers of the primary particles of the precursor in Comparative Example 2 are small, but the stacking is relatively dense, the secondary particle size distribution is wide, and there are more small particles, which cannot meet the requirements of a large specific surface area and is not conducive to improving the electrochemical performance of the positive electrode active material.
[0096] According to Table 2, the positive electrode material prepared by the precursor provided by the present invention is subjected to charge and discharge tests at 25°C and 2.0-4.2V. The capacity retention rate after 50 cycles of charge and discharge at 1C rate is ≥80%, and the discharge specific capacity at 0.1C rate is ≥
[0097] 156mAh / g, discharge specific capacity at 0.2C rate ≥151mAh / g, discharge specific capacity at 0.5C rate ≥148mAh / g, discharge specific capacity at 1C rate ≥144mAh / g, discharge specific capacity at 2C rate ≥141mAh / g.
[0098] It should be noted that the terms "first", "second", etc. in the specification and claims of the present application are used to distinguish similar objects, and are not necessarily used to describe a specific order or sequence. It should be understood that the terms used in this way can be interchangeable where appropriate, so that the embodiments of the present application described herein can be implemented in an order other than those described herein, for example.
[0099] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A positive electrode active material precursor, characterized in that: The positive electrode active material precursor includes secondary large particles assembled from secondary small particles, and the secondary small particles are assembled from primary particles; wherein the ratio of the diameter of the secondary small particles to the diameter of the secondary large particles is (0.09-0.2):
1.
2. The positive electrode active material precursor according to claim 1, characterized in that: The primary particles are flaky whiskers with a length of 300 to 400 nm, a width of 200 to 350 nm, and a thickness of 50 to 70 nm; and / or the specific surface area of the positive electrode active material precursor is 20 to 40 m 2 / g; and / or, the particle size distribution width SPAN value of the positive electrode active material precursor is 0.8 to 1.
35.
3. The positive electrode active material precursor according to claim 1 or 2, characterized in that: The diameter of the secondary small particles is 0.3-1 μm; and / or the diameter of the secondary large particles is 3-7 μm.
4. The positive electrode active material precursor according to claim 1 or 2, characterized in that: The tap density of the positive electrode active material precursor is 1.1 to 1.8 g / cm 3 .
5. The positive electrode active material precursor according to claim 1 or 2, characterized in that: The chemical formula of the positive electrode active material precursor is Ni x Fe y Mn 1-x-y (OH)2, wherein 0.01≤x≤0.8, 0.01≤y≤0.8, 0.01≤1-xy≤0.
8.
6. A method for preparing a positive electrode active material precursor according to any one of claims 1 to 5, characterized in that: The method comprises the following steps: mixing a metal salt solution, a precipitant and a complexing agent to form a reaction slurry, and subjecting the reaction slurry to a coprecipitation reaction to obtain a positive electrode active material precursor; wherein, in the coprecipitation reaction, the rotation speed of the reaction slurry is controlled to be 50 to 500 rpm, the pH value is controlled to be 7 to 12, and the reaction temperature is controlled to be 30 to 80°C.
7. The preparation method according to claim 6, characterized in that: The concentration of metal ions in the metal salt solution is 0.5-4 mol / L; and / or the complexing agent includes at least one of ammonia water, EDTA, triethanolamine, ammonium citrate, glycine, sodium citrate, tartaric acid, citric acid, ethylenediamine, ethanolamine, and acetic acid; and / or the precipitating agent includes at least one of sodium carbonate, sodium bicarbonate, ammonium bicarbonate, sodium oxalate, sodium hydroxide, and potassium hydroxide.
8. The preparation method according to claim 6 or 7, characterized in that: The molar ratio of the precipitant to the metal ions in the metal salt solution is (1-2.2):
1.
9. The preparation method according to claim 6 or 7, characterized in that: After the coprecipitation reaction, the method further comprises the following steps: centrifugally washing the material after the coprecipitation reaction in an alkali solution of 0.8 to 8 mol / L at a speed of 5 to 20 rpm, then washing with distilled water at the same speed, and finally drying the washed material at 60 to 150° C. for 10 to 40 hours.
10. A sodium battery positive electrode material, characterized in that: The positive electrode active material precursor is prepared by sintering raw materials including a positive electrode active material precursor, wherein the positive electrode active material precursor includes the positive electrode active material precursor according to any one of claims 1 to 5 or the positive electrode active material precursor prepared by the preparation method according to any one of claims 6 to 9.
